The Structural Transformation of Land Administration Institutions in Aceh Province within the Framework of Public Land Administration Services Based on the General Principles of Good Governance (AAUPB) - F.X. Arsin Lukman; Muhammmad Farhan Al Ghalib (UIN Sunan Kalijaga Yogyakarta, 2025)
This study examines the structural changes in land administration institutions in Aceh Province within the framework of land administration services based on the General Principles of Good Governance (AAUPB). The background of this research lies in Aceh’s special autonomy status, which grants authority over land management under Law Number 11 of 2006 concerning the Governance of Aceh. The research method applied is normative juridical, employing a statutory approach, a conceptual approach, and supported by interviews with relevant stakeholders. The findings indicate that the structural change positions the Aceh Land Agency (Dinas Pertanahan Aceh) as responsible for policy formulation and customary land management, while the Aceh branch of the National Land Agency (BPN Aceh) focuses on technical services such as land registration. The implementation of AAUPB principles—such as legal certainty, transparency, and accountability—has been applied, although challenges remain, including regulatory disharmony and limited integration of information systems. The study recommends accelerating the enactment of the Aceh Land Qanun, harmonizing regulations, and digitalizing land services. Keywords: Institutional Change, Land Administration, Aceh, AAUPB, Aceh Land Qanun